Failure Analysis and Microstructural Evolution of Fibre Laser Welded Dissimilar Al Alloy Joints - Baqer Y.M.; Ramesh S.; Yusof F.; Ibrahim M.Z. (Old City Publishing, 2025)
Due to their outstanding corrosion resistance, mechanical characteristics and low specific density, AA5083 and AA6061-T6 Al alloys are used in the aerospace, automotive and marine sectors. Joining such dissimilar Al alloys using conventional fusion welding techniques is very challenging. In contrast, laser beam welding (LBW) is a non-conventional welding technique that is promising to weld dissimilar materials. The viability of welding dissimilar AA5083 and AA6061-T6 joints using fibre laser welding are examined herein. The effect of laser power and welding speed on the morphological, microstructural, microhardness and tensile strength of the welded joints was assessed and revealed that increasing welding power resulted in deeper keyhole penetration. Microporosities were formed due to Mg evaporation and shrinkages; however, the existence of these porosities did not show significant effect on the tensile strength. The microhardness values indicate that the welds were harder than the AA6061 and AA5083 base metals. This is explained by the existence of Mg2Si phase in the AA5083-AA6061 dissimilar junction in addition to the grain size circumstances. The fracture examination showed brittle fracture pattern that is regarded to the formation of brittle intermetallic compound (IMC) phases of Mg2Si, in addition to the inter-dendritic brittle phases of other sites as they were frequently inter-granular. ? 2024 Old City Publishing, Inc.